Que recouvre la fonction d'enseignant référent ? Cartographie d'une activité - Matthieu Laville (Nantes Université, 2018)
Since the beginning of the 2006 academic year, teacher-referents have been responsible for following the journey of the schooling of students with disabilities by coordinating the actions of various partners via the ESS meetings ('Équipes de suivi de scolarisation' in French). Based on certain sociological approaches of professional groups and on analysis of work, this article aims to study the concrete work of the teacher-referent. It proposes to evaluate its role against the requirements framing this profession. The article will then outline the steps that marked the gradual transition from an exploratory ethnography to the building of a nationwide questionnaire. The results highlight the sometimes differing interpretations of these requirements and result in a cartography of the main areas of work. It finally allows us to capture the determining factors which most influence the prevalence of ESS programming.